2016
DOI: 10.1164/rccm.201511-2205oc
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CD4+ T Cell–Dependent Murine Model of Pneumocystis-driven Asthma-like Pathology

Abstract: Rationale: Infection with Pneumocystis, an opportunistic fungal pathogen, can result in fulminant pneumonia in the clinical setting of patients with immunosuppression. In murine models, Pneumocystis has previously been shown to induce a CD4 1 T cell-dependent eosinophilic response in the lung capable of providing protection.Objectives: We sought to explore the role of Pneumocystis in generating asthma-like lung pathology, given the natural eosinophilic response to infection.Methods: Pneumocystis infection or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 61 publications
4
57
0
Order By: Relevance
“…S7F,G). Furthermore, in agreement with previously published data in a sterile Pneumocystis antigen model (Eddens et al, 2016), the T-cell responses were unperturbed in dblGATA1 −/− mice (Fig. S7G).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S7F,G). Furthermore, in agreement with previously published data in a sterile Pneumocystis antigen model (Eddens et al, 2016), the T-cell responses were unperturbed in dblGATA1 −/− mice (Fig. S7G).…”
Section: Resultssupporting
confidence: 92%
“…Colonization with Pneumocystis in these infants was associated with increases in a chloride channel associated with mucus release, suggestive of potential pathologic response to the fungus (Pérez et al, 2014). Likewise, we have previously demonstrated that Pneumocystis exposure in mice led to asthma-like pathology, and that a subset of patients with severe asthma had increased antibody responses against Pneumocystis (Eddens et al, 2016). …”
Section: Introductionmentioning
confidence: 87%
“…Additional patient groups at risk are patients with connective tissue disease with vasculitis or polymyositis/dermatomyositis. In addition treatments targeting B-cells in cancer or in autoimmune inflammation with anti-CD20 have been associated with Pneumocystis infection [9, 10]. This has been modelled in the mouse where anti-CD20 could perturb CD4 + T-cell priming and enhance susceptibility to infection [11].…”
Section: Current Epidemiology Of Pneumocystis Infectionmentioning
confidence: 99%
“…In an immunocompromised host, components of aTh2-driven immune response have proven to be beneficial. In contrast, Th2 responses to Pneumocystis drive inflammation and asthma-like pathology in healthy individuals comparable to that of the common allergen, house dust mite [9]. Therefore, a consequence of chronic exposure to Pneumocystis could indeed be asthma.…”
Section: The Role Of Cell-mediated Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation